The Analysis Factor Influence Quality of Life Erderly People in Lemper Pamekasan City - Nindawi Nindawi (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2019)
Increasing the number of Elderly impact on various life and increasing dependence and can be a burden for the family, because each individual has a unique and different characters. Coping mechanisms and adaptation processes need to be studied and strived for independent living with good quality of life to meet daily needs. This study aims to analyze the factors that affect the quality of life of the Elderly in Lemper Pamekasan Village. This research use cross sectional. Population (N = 176) sample (n = 122) Elderly Age (60-74 years) / erderly with Simple Random Sampling technique. Independent variable (physical activity, psychological, socialization, family support, and spiritual needs) to the dependent variable (quality of life) by using questionnaire in Lemper Pamekasan Village in February 2018. Data were processed and analyzed multivariate by ordinal regression test. Based on the result of research from 122 respondents it is found that the characteristics of respondents based on gender are mostly 71 (58,2%), almost half of them 65-69 years old 59 (48,4%), mostly married 67 (54,9% ), most worked 67 (54.9%), and most health status was ill as much as 79 (64.8%). Most of the physical activity is good as much as 80 (65,6%), mostly psychological enough 65 (53,3%), almost half enough (47,5%), almost half socialization enough 58 (47,5%), most of the family support is less than 87 (71.3%), most of the spiritual needs are good as much as 75 (61.5%), and most of the quality of life is quite 89 (73,0%). The variables that significantly influence the quality of life of the Elderly are physical activity (p = 0.028), and family support (p = 0,024), while psychological (p = 0,463), socialization (p = 0,529), and spiritual requirement (p = 0,055) no influence. Simultaneously family support is a dominant factor. The influence of family support needs to be followed up with the development of the elderly program is expected to involve Elderly families to improve the quality of life. The Elderly can integrate and adapt to the changes that he experienced physically, spychologically, and socially, as well as enjoying his daily life in a healthy, fit, prosperous and productive way. Health workers may undertake the role of motivators to participate in the nearest health service program to improve the health of the Elderly in an optimal and comprehensive manner.